E-Assessment of Case Method and Team-Based Project (TBP) in Education 5.0 to improve Students’ Academic Writing in University - Rita Suswati; Mahmud Layan Hutasuhut; Ade Aini Nuran; Dini Sianturi (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2025)
Integrating an e-assessment model based on the Case Method and Team-Based Project (TBP) will enhance academic writing skills among university students in the Contextual Writing Language Skills (CWLS) course. This study addresses the challenges experienced by the students in organizing ideas, employing accurate grammar, and developing logical arguments in writing. Utilizing a Research and Development (R&D) method, the study involved a sample of 25 students who participated in e-assessments research. They provided their immediate feedback and personalized learning experiences. The findings indicated a significant improvement in students’ writing abilities, with an increase of 27.4% in the students’ average post-test scores. This suggests that digital e-assessment not only improved student performance but also aligned with the principles of Outcome-Based Education (OBE) to give significant outcomes in the learning process. The research concludes that adopting digital technology in pedagogical practices can significantly elevate students' academic skills, contributing to more effective teaching and learning environments in higher education.